2019
DOI: 10.1002/anie.201908931
|View full text |Cite
|
Sign up to set email alerts
|

H2‐Acceptorless Dehydrogenative Boration and Transfer Boration of Alkenes Enabled by Zirconium Catalyst

Abstract: Scheme 1. Methodsf or transition-metal-catalyzed synthesis of vinyl boronate esters:a )dehydrogenative boration of alkenes in the presence of hydrogen acceptors;b)"dehydrogenative" boration of alkenes using B 2 pin 2 ;c)our current methodologies. Scheme 3. Practical synthetic application of vinyl boronate esters. a) Cu(OAc) 2 ,Et 3 N, air,EtOH, 25 8 8C; b) Cu(OAc) 2 ,D MF/EtOH, air, 25 8 8C; c) KHF 2 ,H 2 O/MeOH,0 -25 8 8C; d) I 2 ,N aOH, Et 2 O, 25 8 8C; e) 4-Iodoanisole, Pd(dba) 2 , tBu 3 P, THF, 25 8 8C; f)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 93 publications
2
33
0
Order By: Relevance
“…Taking into consideration the significant importance of vinylboronates in organic synthesis and their extensive applications in the preparation of pharmaceuticals, biologically active molecules, functional material molecules, and polymers, an efficient synthesis of vinylboronates is highly desirable. Conventionally, vinylboronates were prepared from alkynes via hydroboration or from alkenes via dehydrogenative borylation. , The deoxygenative borylation of ketones would be an important complement to the existing protocols for the preparation of vinylboronates, and enrich the potential of ketones as well. To this end, we optimized the deoxygenative borylation reaction using acetophenone as the model substrate.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Taking into consideration the significant importance of vinylboronates in organic synthesis and their extensive applications in the preparation of pharmaceuticals, biologically active molecules, functional material molecules, and polymers, an efficient synthesis of vinylboronates is highly desirable. Conventionally, vinylboronates were prepared from alkynes via hydroboration or from alkenes via dehydrogenative borylation. , The deoxygenative borylation of ketones would be an important complement to the existing protocols for the preparation of vinylboronates, and enrich the potential of ketones as well. To this end, we optimized the deoxygenative borylation reaction using acetophenone as the model substrate.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Next, in 2019 for the first time, the Wu group demonstrated that the Cp 2 ZrH 2 acts as a catalyst in the dehydrogenative borylation of alkenes (Scheme 7b) [28] . This protocol overcomes the drawbacks of previously reported protocols, such as using precious transition metals or HB(pin) scavengers [29] .…”
Section: Reaction With Alkenementioning
confidence: 91%
“…We then found that the reaction was general to a series of aryl alkenes with alkyl, aryl, dimethylamino, halo, or trifluoromethyl substituents on the phenyl ring (22-29; up to 99% yield) (Scheme 16), and for most of the substrates, the reaction was complete within one hour. 38 A substrate with an ester group gave only 9% of the corresponding VBE 30, whereas -methylstyrene gave the expected product 32 in 67% yield at 100 ℃. Interestingly, the protic NH 2 group, which was expected to react with HBpin, survived, and product 31 was obtained in 93% yield.…”
Section: Scheme 15 Homogeneous and Heterogeneous Copper-catalyzed Dehmentioning
confidence: 99%